A MICROCONTROLLER BASED APPROACH TO THE SOLAR TRACKING CHARACTERIZATION - MR. DEVENDRA D. PATIL; PROF. R. H. MADHAVI (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Solar energy is imperative method for growing renewable energy resources. In this paper is portrayed the plan and development of a microcontroller based solar board following system. Solar is a nonconventional wellspring of energy, considering this we have created solar boards with the goal that we can satisfy our electricity required. Be that as it may, because of transformation of the earth, solar source i.e. sun does not confront the board persistently consequently less electricity is delivered. The energy board ought to confront the SUN till it is available in a day. The issue above can be understood by our system via programmed following the solar energy. The block outline beneath shows system design it comprise of a LDR sensor detects max solar power which is being given to the Microcontroller through the ADC which digitizes the LDR output. Controller then takes the choice as indicated by then calculation and tilts the board towards the bearing of the maximum energy given by LDR with the assistance of DC Motor. The Motor is utilized to turn the LDR to detect the maximum solar power. A Solar Tracker is fundamentally a gadget onto which solar boards are fitted which tracks the movement of the sun over the sky guaranteeing that the greatest measure of sunlight strikes the boards for the duration of the day. In the wake of finding the sunlight, the tracker will attempt to explore through the way guaranteeing the best sunlight is recognized. It is totally programmed and keeps the board before sun until that is obvious. Its dynamic sensors always screen the sunlight and turn the board towards the course where the power of sunlight is greatest. Private that utilizations solar power as their option power supply will convey advantages to them.